Strategi Pemasaran Minyak Kelapa Murni di Kabupaten Bantul Yogyakarta - Putra, Muhammad Fadhilah; Ismiasih, Ismiasih; Ferhat, Amallia (MARGIN ECO, 2024)
This research aims to determine the marketing strategy for pure coconut oil, and determine the internal and external factors that hinder the marketing of pure coconut oil. The research method uses a qualitative descriptive method. The sample was determined using purposive sampling, namely by taking three samples of pure coconut oil producers located in the Bantul Regency area, Yogyakarta. Data was analyzed using the SWOT method. The research results show that the marketing strategy carried out is by utilizing internal strengths, namely by promoting products through social media and taking advantage of opportunities by collaborating with companies as partners in marketing. The obstacles that become obstacles in marketing pure coconut oil are internal factors such as the price which is quite expensive and external factors, namely competition from producers of similar products from outside the city and within the city